2018
DOI: 10.35530/it.069.01.1380
|View full text |Cite
|
Sign up to set email alerts
|

Developing a modular apparel safety architecture for supply chain management: the apparel recycle perspective

Abstract: Cuvinte-cheie: siguranța îmbrăcămintei, sistem de îmbrăcăminte reciclabilă, design modular, managementul lanțului de aprovizionare Developing a modular apparel safety architecture for supply chain management: the apparel recycle perspectiveThis paper introduces the special issue on strategic choices for recyclable clothing implementation. Substantial private implementation is needed if company management objectives to increase the share of recyclable clothing and prevent dangerous clothing risk be achieved. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…(2019) identified opportunities to improve the use of reverse logistics in the clothing industry. Likewise, Lihong et al. (2018) developed a modular apparel safety architecture for supply chain management from the apparel recycling perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) identified opportunities to improve the use of reverse logistics in the clothing industry. Likewise, Lihong et al. (2018) developed a modular apparel safety architecture for supply chain management from the apparel recycling perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pinheiro et al (2019) identified opportunities to improve the use of reverse logistics in the clothing industry. Likewise, Lihong et al (2018) developed a modular apparel safety architecture for supply chain management from the apparel recycling perspective. Riemens et al (2021) explored the challenges of textile recycling in Europe for the clothing industry.…”
Section: Literature Review 21 Recycling Supply Chain Management In Th...mentioning
confidence: 99%